Cauliflower (Larissa F1) Response to Media Composition and Liquid Organic Fertilizer under Limited Land Condition in Bogem, Sidoarjo - Pratiwi, An Nisa Eka; Nugrahani, Pangesti; Sulistyono, Agus (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background : Cauliflower (Brassica oleracea L.) is a highly valued horticultural vegetable comodity. Previous research on the application of Jimmy Hantu LOF on cauliflower has focused on the polybag planting system with a single type of media, whereas this study focuses on the variation in planting medium composition (soil, goat dung, and burnt husks) in conjunction with LOF concentration. This method is expected to provide more thorough information regarding the interaction between growing media and liquid organic fertilizer as a strategy to boost cauliflower productivity in limited land settings. Methodology: The research was carried out at Sidoarjo, East Java. Polybags with various liquid organic fertilizer compositions and dosages were used in this research. The study used a completely randomized factorial design with two treatment factors: the kind of planting media (three treatment levels) and the concentration of liquid fertilizer (four treatment levels). Findings: There was a significant interaction between the soil composition treatment goat manure: burnt husks (1:1:1) (M2) and the content of liquid organic fertilizer 14 ml/L (P3) when compared to the control treatment. The treatment resulted in a 34.42 % difference in the height of cauliflower plants and a 44.93 % difference in the number of leaves. The results show that combination of planting medium soil: goat manure: burnt husk (1:1:1) (M2) with the application of 14 ml/L of Jimmy Hantu liquid organic fertilizer is the most successful treatment. Contribution: These findings provide scientific evidence on the synergistic effect of planting media composition and liquid organic fertilizer concentration, offering a valuable reference for optimizing sustainable B. oleracea cultivation in limited land conditions